Challenges and Opportunities of Divorce Certificates in Determining the Iddah Period: A Case Study at the KUA of West Kotawaringin Regency - Suparliyah, Tri; Helim, Abdul; Hidayati, Tri (Journal of Education and Religious Studies, 2024)
This study aims to analyze the role of Akta Cerai in determining the iddah period and identify the challenges and opportunities faced by the Office of Religious Affairs (KUA) of West Kotawaringin Regency in the context of divorce administration. The researcher uses a qualitative approach with a case study method, and this research combines in-depth interviews, direct observation, and analysis of relevant documents to map the dynamics of divorce registration practices in the area. The results show that one of the main challenges is the discrepancy between the date of the shar’i divorce and the date of the official recording in the Deed of Divorce, which often results in legal uncertainty for women regarding their rights during the iddah period. This phenomenon is exacerbated by factors such as the lack of public legal awareness, limited technological infrastructure at the KUA, and the high workload of administrative officers. On the other hand, the study also found several opportunities for system improvement, including using digital technology through the SIAP Nikah application and collaboration with local religious institutions to improve community legal literacy. The article highlights the importance of harmonization between Islamic legal principles and state administrative regulations in ensuring gender justice and the protection of family rights. Strategic recommendations include strengthening the capacity of KUAs through officer training, equitable integration of digital systems, and intensive socialization of fiqh iddah and divorce administrative procedures. Further research is needed to evaluate the effectiveness of technology implementation and the social impact of related policy interventions.